Strategi Dan Urgensi Perencanaan Bisnis Dalam Pengembangan Usaha Mikro, Kecil, Dan Menengah (UMKM) - Zida Maghfiroh; Kharina Arifia (Cashless : Journal of Sharia Finance and Banking, 2025)
Business planning is a crucial foundation for business sustainability amidst competitive market dynamics. This article aims to analyze the key components of business planning, including marketing, operations, risk management, and financial projections. Using a descriptive qualitative approach, this study evaluates the role of SWOT analysis and business feasibility parameters such as the Break Even Point (BEP) in minimizing business failure. The study results indicate that integrated planning facilitates operational oversight, optimizes capital allocation, and assists entrepreneurs in strategic decision-making. A strong business plan has proven to be a roadmap for sustainable business growth.